“Nevertheless She Persisted:” Confronting the Silencing and Reproduction of Gender-Based Violence among U.S. Asylum Seekers - Garni, Alisa (Victims & offenders, 2023)
Gender-based violence is a pervasive global crisis that affects people in myriad ways. Little is known about the impact of victimization experiences of one particularly vulnerable group: women who are “defensively” seeking asylum in the United States. Our ethnographic research with asylum seekers and legal advocates reveals how systems of oppression interact across borders to multiply women’s vulnerability to victimization, obstruct their access to critical resources, bar their flight and safe passage, and restrict their access to asylum. We urge recognizing gender as a protected ground for asylum and enforcing robust rights and protections for women transnationally.